Respuesta :

Answer:

(x-2)

Step-by-step explanation:

Given expression is [tex]\frac{(x+1)^2-9}{x+4}[/tex]

Now we factor the given expression

LEts factor the numerator

(x+1)^2 -9

9 can be written as 3^2

(x+1)^2 - 3^2

Now we apply a^2 - b^2 formula

a^2 - b^2 = (a+b)(a-b)

(x+1)^2 - 3^2 = (x+1+3)(x+1-3)=(x+4)(x-2)

now we replace it in our problem

[tex]\frac{(x+1)^2-9}{x+4}=\frac{(x+4)(x-2)}{x+4}[/tex]

Cancel out x+4 from top and bottom

So answer is (x-2)

Answer:

(x-2)

Step-by-step explanation:

correct on edge 2021

-RZA

ACCESS MORE